Clinical InvestigationsComparison of 2D- and 3D-guided implantation in accelerated partial breast irradiation (APBI) - Cholewka, Agnieszka; Szlag, Marta; Ślosarek, Krzysztof; Białas, Brygida (Journal of Contemporary Brachytherapy, 2009)
Purpose: In this study two different pre-planning methods (2D vs. 3D) were compared in respect to the implant quality as judged by volumetric and dose parameters of the treatment plans. The aim of this work was to evaluate the influence of the imaging modalities used for pre-planning purpose to the treatment plan quality. Material and methods: Twenty-four patients treated with HDR multicatheter implants were randomly selected for experiment. All patients underwent breast conserving surgery. Flexible catheters were implanted into the breast through the template. Inter-catheter distance, number of planes and catheters were adjusted, in respect to the size and location of the target. Pre-planning was used to evaluate the implant geometry in respect to the target. Needles number and position were modified if necessary. There were two experimental subgroups consisted of 12 patients each. Different pre-planning procedure was employed in each group. In the first group 2D X-ray imaging system was used. In the second one the 3D pre-planning method based on CT was performed. Treatment plans were evaluated with parameters calculated based on dose-volume histograms (DVHs). Volumetric and dose parameters were used for comparison of the dose distribution between the two experimental subgroups. Results: The mean value of target coverage VPTV100 is higher for 3D pre-planning than for 2D (91.7% vs. 86.1%). The dose that covers 90% of the PTV (D90) is also higher for 3D pre-planning than for 2D (4.2 Gy vs. 3.6 Gy). Similar relation can be observed for the values of dose homogeneity index where DHI obtained for 3D pre-planning is 0.60 and 0.53 for 2D. All differences were statistically significant with p < 0.05. Conclusions: Analysis presented in this paper showed that 3D pre-planning method improves the geometrical quality of the implant.